2010
DOI: 10.1007/s10267-009-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Three new Ceratocystis spp. in the Ceratocystis moniliformis complex from wounds on Acacia mangium and A. crassicarpa

Abstract: The genus Ceratocystis includes many important tree pathogens and agents of sap stain. These fungi have a global distribution and commonly infect wounds on trees. During a survey of woundinfecting pathogens in the genus Ceratocystis on plantation-grown Acacia mangium trees in Indonesia, several isolates resembling Ceratocystis moniliformis sensu lato (s.l.) were obtained. The aim of this study was to identify these isolates and to test their pathogenicity on commercially grown Acacia spp. in the country. Use w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
(25 reference statements)
1
28
0
3
Order By: Relevance
“…Experiments where trees in natural forests or plantations were wounded (e.g. Geldenhuis et al 2004;Roux et al 2004Roux et al , 2007Tarigan et al 2010) have confirmed the ability of these fungi to infect trees through these wounds. In general, natural infections might be the result of wind or rain splash dispersal of spores, or by transmission of inoculum by arthropod vectors such as bark beetles, nitidulid beetles and mites (Malloch and Blackwell 1993;Six 2003;Klepzig and Six 2004;Hayslett et al 2008;Juzwik et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Experiments where trees in natural forests or plantations were wounded (e.g. Geldenhuis et al 2004;Roux et al 2004Roux et al , 2007Tarigan et al 2010) have confirmed the ability of these fungi to infect trees through these wounds. In general, natural infections might be the result of wind or rain splash dispersal of spores, or by transmission of inoculum by arthropod vectors such as bark beetles, nitidulid beetles and mites (Malloch and Blackwell 1993;Six 2003;Klepzig and Six 2004;Hayslett et al 2008;Juzwik et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…: Three new species of Ceratocystis have recently been described associated with a serious disease of young A. mangium trees, which developed after pruning in the Riau area, Sumatra (Tarigan et al 2011). In a recent survey, C. acaciivora (Figure 8a) was found on dying A. mangium in the absence of pruning wounds.…”
Section: Major Pathogens Of Acaciamentioning
confidence: 97%
“…The productivity in our experiments also compared favourably with Eucalyptus productivity in Brazil reported by Stape et al (2010), who found average MAIs of 46 m 3 ha -1 year -1 across eight locations with fertiliser applied but no irrigation. However, it does need to be recognised that acacias are no longer a preferred species in Sumatra because of their susceptibility to Ganoderma root rot (Glen et al 2009) and Ceratocystis fungal wilt (Tarigan et al 2010), and these growth rates are no longer achievable with A. mangium.…”
Section: Discussionmentioning
confidence: 99%